The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/cbf.1235
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron and copper status and oxidative stress in severe and mild preeclampsia

Abstract: Our aim was to investigate parameters of iron and copper status and oxidative stress and antioxidant function in women with healthy pregnancy, mild and severe preeclampsia with a view to exploring the possible contribution of these parameters to the aetiology. Thirty healthy, 30 mild preeclamptic and 30 severe preeclamptic pregnant women were included. Serum and placental lipid peroxides, and serum vitamin E and total carotene levels were measured by colorimetric assay. Cholesterol, copper, iron, total iron bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 50 publications
6
52
0
1
Order By: Relevance
“…Similarly to our patients, women with severe preeclampsia presented higher levels of lipid peroxidation and serum CP, and lower levels of Tf with respect to pregnant women healthy or with mild preeclampsia. [43][44] These findings suggest that CP/Tf system is involved in the oxidative stress generated in different body districts.…”
Section: Altamura Et Al Transferrin and Ceruloplasmin In Acute Strokementioning
confidence: 86%
See 1 more Smart Citation
“…Similarly to our patients, women with severe preeclampsia presented higher levels of lipid peroxidation and serum CP, and lower levels of Tf with respect to pregnant women healthy or with mild preeclampsia. [43][44] These findings suggest that CP/Tf system is involved in the oxidative stress generated in different body districts.…”
Section: Altamura Et Al Transferrin and Ceruloplasmin In Acute Strokementioning
confidence: 86%
“…44,Pϭ0.012). No evidence of association between CP, Tf, Cu, "free" Cu, Fe, Ferritin, TAS, as well as NIHSS, with inflammation markers was found (all PϾ0.2, apart from CP and fibrinogen: rϭ0.37, Pϭ0.061).…”
Section: )mentioning
confidence: 98%
“…Furthermore, serum levels of lipid peroxides, iron, and ceruloplasmin in severe preeclampsia are elevated, whereas the transferrin level was decreased; ischemic placental tissue was proposed to be a primary source of toxic iron in preeclampsia. 67 There are limitations of this study. First, although we report a robust increase in miR-210 expression in the villous placental tissues of preterm preeclampsia and SGA cases, increased iron deposition in trophoblasts after hypoxia and ISCU knockdown was found only in Swan 71 cells with an extravillous trophoblast phenotype and in placental bed interstitial trophoblasts.…”
mentioning
confidence: 88%
“…[7][8][9] Trace elements are necessary to biological processes in human Several trace elements and oxidant/antioxidant status have been implicated in the pathogenesis of preeclampsia. [13][14][15][16] In several of studies, trace element ratios have been used as an index related to increased inflammation and oxidative stress in the development or progression of the disease activities. However, there are various of studies in the literature, in which preeclamptic patients disclose the relationship of some characteristic features, trace element levels and oxidative stress parameters.…”
Section: Introductionmentioning
confidence: 99%
“…16,20 It has been suggested that transition metals, The disturbance of the prooxidant/antioxidant balance that results from increased free radical production, antioxidant enzyme inactivation, and excessive antioxidant consumption is the causative factor in oxidative damage. Oxidative stress is an important mediator of abnormal platelet function and dysfunctional endothelium-dependent vasodilation in the setting of cardiovascular disease.…”
mentioning
confidence: 99%